Utilization of fermented corn cob flour with "MOIYL" probiotics on local rabbit performance - Irianto Arswandi; Yunilas .; Sayed Umar; Armyn Hakim Daulay; Ma'ruf Tafsin (Jurnal Peternakan Integratif, 2019)
The study aims to evaluated thedetermine the effect of gave fermented corncob by probiotic MOIYL to performance of local rabbit. Research conducted at DesaBandar Klippa Deli Serdang and Agriculture Faculty of North Sumatera University, inJanuary – March 2018. The study used design experiment by completely randomizeddesign (CDR), which consists of 4 treatments and five replications. The treatmentconsisted of ration P0= unfermented ,P1 (10% corn cob fermented and 20%unfermented), P2 (20% corn cob fermented and 10% unfermented), and P3 (30% corncob fermented). Variable measured were feed consumption, daily body weight gain,feed conversion ratio and income over feed cost.The results showed that fermented ofcorn cob with probiotics MOIYL provide a significant effect (P<0,05) towards bodyweight gain, consumption and Income Over Feed Cost and does not have an effect (P>0.05) on the value of conversion. The conclusion from the results of this study is theprovision of fermented corn cobs using MOIYL can increase body weight gain,consumption and Income Over Feed Cost, and tend to reduce the value of feedconversion.